Computing high dimensional multiple integrals involving matrix exponentials - Naranjo-Noda, F.S.; Jimenez, J.C. (Journal of computational and applied mathematics, 2023)
This paper deals with the numerical computation of the high dimensional multiple integrals involving matrix exponentials that can be rewritten as the product of a matrix exponential times vector. To this end, in addition to the conventional iterative methods for computing the action of the matrix exponential on a vector, iterative methods for the action of the phi-function over a vector are also considered. This is illustrated with a Krylov–Padé approximation to the product of phi-function times vector, which reveals potential for computing a variety of high dimensional multiple integrals that arise in several areas of applied mathematics, model identification, control engineering and numerical methods. •Computation of high dimensional multiple integrals involving matrix exponentials.•High order Krylov–Padé approximation for the action of the matrix exponential.•Error-based estimation of Krylov subspace dimension and Padé order.•High computational efficiency.